Bella 'D / Hanies Nazariah Awang... [et al.] - Suliman, Fatiha; Lazim, Suhaila; Rosdi, Didi Nabila; Awang, Hanies Nazariah (2013)
Bella 'Dis to be established on March 2013. This company is in field producing product which is producing handbag. Our main focus on producing product from denim, we choose this type of business after considering the market trend and the future prospect of the business . As usual, denim is using to produce clothes, jacket and jeans but handbag from denim is not familiar in market. It is different from others varieties handbag in market. The market for handbag made from denim is still not explored or growth mature in market trend in this country. The quality of denim is a main source in producing our handbag. We have chosen this business because handbag can be consider as one of important thing in women life. The statistics pertaining to handbag from original denim is not available in our country market. The consumer will get handbag from original denim but is too expensive in price and its will take time if it involve in importing from other country. Although in view of its market in our nation the potential is high. It is a big chance for us to manufacture and marketing the handbag from denim and we planned to expand our business to whole Sabah. Nevertheless, when we successful we would like to take an opportunity to become main supplier in Malaysia.